La0.7Sr0.3MnO3 nanoparticles coated with fatty amine - Rajagopal, Rajashree; Mona, J.; Kale, Sangeeta N.; Bala, Tanushree; Pasricha, Rem; Poddar, P.; Sastry, M.; Bhagavatula L. V. Prasad; Kundaliya, Darshan C.; Ogale, S. B. (Applied Physics Letters, 2006)
We report on the synthesis of La0.7Sr0.3MnO3 (LSMO) nanoparticles having perovskite structure and particle size of the order of 30 rim. The process involves citrate-gel synthesis, size filtering, and; surface coating with a shell of octadecyl amine (ODA) using electrostatic interaction-assisted novel chemical route. Magnetic measurements show the Curie temperature of similar to 360 K establishing the desired stoichiometry and phase. Fourier transform infrared-studies bring out. that the amine group of ODA interacts with the LSMO surface. Refluidization yields uniform redispersion of the coated and dried powder. (c) 2006 American Institute of Physics.

Magnetic transition and large magnetocaloric effect associated with surface spin disorder in Co and CocoreAgshell nanoparticles - Poddar, P.; Srinath, S.; Gass, James; Bhagavatula L. V. Prasad; Srikanth, H. (Journal of Physical Chemistry C, 2007)
We report a reversible, large magnetocaloric effect in the vicinity of a low-temperature magnetic transition in Co and CocoreAgshell nanoparticles synthesized using a wet chemical method. The as-synthesized assembly of the particles shows a sharp low-temperature peak in the zero-field-cooled (ZFC) magnetization well below the blocking transition temperature, and this feature is associated with the surface spin disorder. Co nanoparticles show a large increase in the magnetic entropy at around 15 K with a peak value of nearly 2.25 J/K center dot kg for an applied field of 30 kOe. A similar trend is also observed in the silver-coated Co particles. These are some of the largest NICE values observed in nanoparticles to date. The features are ascribed to the low-temperature spin-glass-like freezing transition associated with the surface spins in the shell region that is distinct from the behavior of core spins. Our studies reveal that manipulating the surface anisotropy in core-shell nanoparticles has the potential to lead to a large NICE effect and thus prove to be useful for magnetic refrigeration.

Static and dynamic magnetic properties of Co nanoparticles - Srinath, S.; Poddar, P.; Sidhaye, Deepti S.; Bhagavatula L. V. Prasad; Gass, James; Srikanth, H. (Journal of Nanoscience and Nanotechnology, 2008)
Co nanoparticles have been synthesized using wet-chemical methods. As-synthesized particles show a sharp low temperature peak in zero-field cooled (ZFC) magnetization well below the blocking transition temperature and this feature is associated with surface spin disorder. We have investigated the dynamic magnetic properties of Co using ac susceptibility and resonant RF transverse susceptibility (TS). We also studied the memory and relaxation effects in these nanoparticle systems. From these measurements we show a typical blocking behavior of an assembly of superparamagnetic nanoparticles with a wide distribution of blocking temperatures. The transverse susceptibility measurements on these particles show the presence of anisotropy even above the blocking temperature. The role of surface anisotropy and the size distribution of the particles on the observed memory and magnetic relaxation effects are discussed.
Keywords: Ac Susceptibility; Co Nanoparticles; Magnetic relaxation; Transverse Susceptibility

Field dependence of the magnetocaloric effect in core-shell nanoparticles - Franco, V.; Conde, A.; Sidhaye, Deepti; Bhagavatula L. V. Prasad; Poddar, P.; Srinath, S.; Phan, M. H.; Srikanth, H. (Journal of Applied Physics, 2010)
The field dependence of the magnetic entropy change peak at the low temperature surface spin freezing transition in chemically synthesized, monodispersed Co, Co-Ag, and Ni-Ag core-shell nanoparticles is studied, with the aim of gaining insight into the critical exponents of this transition. It is evidenced that although the magnitude of the peak entropy change and position of the peak can be tuned by changing the composition and nature (metallic or organic) of the shell and surfactant layers, the characteristics of the spin freezing transition are not altered. The field dependence of the refrigerant capacity also confirms this finding. (C) 2010 American Institute of Physics. [doi: 10.1063/1.3335514]

Spin-coatable, photopatternable magnetic nanocomposite thin films for MEMS device applications - Kandpal, Manoj; Sharan, C.; Palaparthy, V.; Tiwary, N.; Poddar, P.; Rao, V. Ramgopal (RSC Advances, 2015)
Magnetic nanomaterials' (especially metals) air stability and compatibility with standard micro-fabrication technologies are often a concern for development of MEMS-based magnetic devices. In this paper, we report an air-stable, photo-patternable and spin-coatable magnetic thin film preparation process for MEMS applications. This magnetic nanocomposite thin film was prepared by incorporating carbon capped ferromagnetic cobalt nanoparticles of dimension 20-80 nm into the SU-8 matrix. TEM, XRD and EDAX analyses were done, to investigate the crystal structure, dispersion and phase stability of the films. The SQUID magnetometry and MFM measurements of the film confirmed its magnetic response at room temperature and the retention of its magnetic properties over a period of time. The material compatibility for MEMS device applications was demonstrated through fabrication of a suspended circular membrane of radius similar to 250 mu m, having four U-shaped beams, of dimension similar to 270 x 50 mu m each. Three conventional lithography steps and a sacrificial release layer of similar to 1 mm thick oxide was used for the fabrication. The membrane was characterized by evaluating its spring constant and resonant frequency. The spring constant and resonant frequencies were estimated to be similar to 4.2 N m(-1) and similar to 29 kHz respectively. Finally, we demonstrated the actuation of the magnetic membrane by an off-chip generated magnetic field, for its possible use as a MEMS device.

Global conformation of Tau protein mapped by Raman spectroscopy - Gorantla, N.V.; Khandelwal, P.; Poddar, P.; Chinnathambi, S. (Methods in Molecular Biology, 2017)
Alzheimer’s disease (AD) is one of the neurodegenerative disease characterized by progressive neuronal loss in the brain. Its two major hallmarks are extracellular senile plaques and intracellular neurofibrillary tangles (NFTs), formed by aggregation of amyloid β-42 (Aβ-42) and Tau protein respectively. Aβ-42 is a transmembrane protein, which is produced after the sequential action of β- and γ-secretases, thus obtained peptide is released extracellularly and gets deposited on the neuron forming senile plaques. NFTs are composed of microtubule-associated protein-Tau (MAPT). Tau protein’s major function is to stabilize the microtubule that provides a track on which the cargo proteins are shuttled and the stabilized microtubule also maintains shape and integrity of the neuronal cell. Tau protein is subjected to various modifications such as phosphorylation, ubiquitination, glycation, acetylation, truncation, glycosylation, deamination, and oxidation; these modifications ultimately lead to its aggregation. Phosphorylation is the major modification and is extensively studied with respect to Tau protein. Tau protein, however, undergoes certain level of phosphorylation and dephosphorylation, which regulates its affinity for microtubule and ultimately leading to microtubule assembly and disassembly. Our main aim was to study the native state of longest isoform of Tau (hTau40WT-4R2N) and its shortest isoform, (hTau23WT-3R0N), at various temperatures such as 10, 25, and 37 °C. Raman spectroscopic results suggested that the proportion of random coils or unordered structure depends on the temperature of the protein environment. Upon increase in the temperature from 10 to 37 °C, the proportion of random coils or unordered structures increased in the case of hTau40WT. However, we did not find a significant effect of temperature on the structure of hTau23WT. This current approach enables one to analyze the global conformation of soluble Tau in solution.

Magnetic studies of SiO2 coated CoFe2O4 nanoparticles - Limaye, M.V. (Journal of Magnetism and Magnetic Materials, 2017)
Oleic acid capped CoFe2O4 nanoparticles which exhibit a high coercivity of ∼9.47 kOe at room temperature were coated with a robust coating of SiO2. We have used chemical synthesis method to obtain SiO2 coated CoFe2O4 nanoparticles with different weight percentages of CoFe2O4 in SiO2 (1.5, 3.1 and 4.8 wt.%). The morphological investigation of the coated nanoparticles by transmission electron microscopy shows that the particles are spherical with average size ∼160 nm. Infrared spectroscopy reveals that oleic acid capping on the surface of CoFe2O4 nanoparticles is retained after silica coating process. The complete coating of SiO2 on CoFe2O4 nanoparticles is confirmed by X-ray photoelectron spectroscopy as there is no signature of cobalt or iron ions on the surface. Magnetic measurements show that coercivity of SiO2 coated CoFe2O4 particles remains more or less unaffected as in CoFe2O4 nanoparticles at room temperature. In addition, the temperature dependent magnetic measurements show that at 5 K the CoFe2O4 and SiO2 coated 1.5 wt.% CoFe2O4 samples exhibit a very high value of coercivity (∼20 kOe) which is more than twice as compared to room temperature coercivity value (∼9.47 kOe). We conclude that silica coating in our study does not significantly affect the coercivity of CoFe2O4 nanoparticles.
Keywords: Coatings; coercive force; High Resolution Transmission Elctron Microscopy; infrared spectroscopy; Magnetic materials

Surface disordered rutile TiO2-graphene quantum dot hybrids: a new multifunctional material with superior photocatalytic and biofilm eradication properties - Biswas, A.; Salunke, G.; Khandelwal, P.; Das, R.; Poddar, P. (New Journal of Chemistry, 2017)
The controlled introduction of defects in semiconductors has contributed to the development of electronic devices and technologies. Recently, chemical control over defects, formation of new hybrid materials and multifunctional nanostructures have been sought in energy, health, and environment related technologies. Surface-disordered anatase-TiO2 has received wide attention due to its exceptional photocatalytic performance. Herein, we demonstrate, for the first time, a one-step aqueous-phase synthesis of a surface-disordered rutile TiO2-graphene quantum dot (TG) hybrid material. The TG-hybrid is a rutile-TiO2 matrix in which homogeneous in situ insertion of GQDs occurs during the growth of the TiO2 particles. The TG-hybrid material showed superior photocatalytic performance with similar to 98% solar light driven photo-degradation of methylene blue (MB) dye within 6 min and similar to 86% of rhodamine-B (RhB) within 4 min which is much better than the photocatalytic performance shown by the rutile-TiO2 (similar to 30% and similar to 20%, respectively) and GQDs (similar to 15% and similar to 8%, respectively), themselves. Moreover, the TG-hybrid also showed enhanced toxicity to Gram-positive (S. aureus) as well as Gram-negative (E. coli, P. aeruginosa) bacterial cells. The growth-curves of E. coli cells, after incubating them with increasing concentrations of the TG-hybrid, showed that the TG-hybrid could effectively inhibit the growth of E. coli cells at a concentration of 60 mu g mL(-1). The effect of UV-light exposure on the bacterial-biofilm disruption by the TG-hybrid material was also investigated. It was observed that in the presence of UV-light, the biofilm disruption done by the TG-hybrid was larger in comparison to the TiO2 and GQDs alone, under the same conditions. The increase in the formation of reactive oxygen species (ROS) in the presence of sunlight for the TG-hybrid may be the reason behind its superior antibacterial and biofilm eradication properties. We believe that the TG-hybrid material will have applications in energy, health and environment related technologies.

Graphene quantum dots-driven multiform morphologies of β-NaYF4:Gd3+/Tb3+ phosphors: the underlying mechanism and their optical properties - Malik, M.; Padhye, P.; Poddar, P. (ACS omega, 2018)
Dimension and shape tunable architectures of inorganic crystals are of extreme interest because of morphology-dependent modulation of the properties of the materials. Herein, for the first time, we present a novel impurity-driven strategy where we studied the influence of in situ incorporation of graphene quantum dots (GQDs) on the growth of β-NaYF4:Gd3+/Tb3+ phosphor crystals via a hydrothermal route. The GQDs function as a nucleation site and by changing the concentration of GQDs, the morphology of β-NaYF4:Gd3+/Tb3+ phosphors was changed from rod to flowerlike structure to disklike structure, without phase transformation. The influence of size and functionalization of GQDs on the size and shape of phosphor crystals were also systematically studied and discussed. Plausible mechanisms of formation of multiform morphologies are proposed based on the heterogeneous nucleation and growth. Most interestingly, the experimental results indicate that the photoluminescence properties of β-NaYF4:Gd3+/Tb3+ phosphor crystals are strongly dependent on the crystallite size and morphology. This study would be suggestive for the precisely controlled growth of inorganic crystals; consequently, it will open new avenues and thus may possess potential applications in the field of materials and biological sciences.

Reversible phase transformation phenomenon in titanium dioxide films: evidence beyond interface-nucleation and dissolution-precipitation kinetics - Gautam, Subodh K.; Singh, Jitendra; Shukla, D. K.; Pippel, E.; Poddar, P.; Singh, Fouran (Acta Materialia, 2018)
The re-crystallization kinetics and rutile to anatase reversible phase transformation (PT) in nano crystalline titanium dioxide (TiO2) are reported. Initially, an amorphous TiO2 film is used for the present study and in situ isothermal annealing dependent nucleation and growth kinetics of anatase and rutile phase is studied at low temperature (similar to 523 K) and well explained using Johnson Mehl AvramiKolmogorov (JMAK) model. The anatase nanocrystallite (NCs) transformation into rutile phase is reported with isothermal annealing for longer time and temperature dependent annealing in lower temperature range 523 K-673 K and explained using interface-nucleation mechanism. Furthermore, the thermodynamic stability of rutile NCs and lattice stress-induced reversible PT in nano-sized rutile TiO2 are confirmed in moderate temperature range (623 K- 973 K) and well explained using x-ray diffraction, micro-Raman spectroscopy and near edge x-ray absorption fine structure spectroscopy studies. However, annealing at higher temperature (1123 K- 1323 K) induces the growth of anatase NCs and their natural transform into rutile phase are explained by well-known dissolution precipitation mechanism. Activation energy of rutile PT is quantified and found higher for dissolution-precipitation mechanism than that for interface nucleation at earlier stage. Thus, overall PT kinetics at different temperature range is well understood by invoking in three step mechanism: 1) early stage anatase-to-rutile transformation is dominated by interface-nucleation, II) then intermediate stage reversible rutile-to-anatase PT and, Ill) at later stages, anatase-to-rutile PT is controlled by dissolution precipitation mechanism. (C) 2018 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Dissolution-precipitation kinetics; Interface-nucleation mechanism; Johnson-Mehl-Avrami-Kolmogorov (JMAK) approach; Reversible phase transformation

Designing multifunctional MOFs using an inorganic motif [Cu3(μ3-OH)(μ-Pyz)] as SBU and their properties - Akhtar, S.; Bala, S.; De, A.; Das, K. S.; Adhikary, A.; Jyotsna, S.; Poddar, P.; Mondal, R. (Crystal Growth & Design, 2019)
In a continuation of our interest in pyrazole-based multifunctional metal-organic frameworks (MOFs), we report herein the construction of a series of Cu(II) MOFs using pyrazole and various 5-substituted isophthalic acids. The central theme is to generate MOFs using the crystal engineering strategy of spacer and node; however, for the node we have introduced a well-known inorganic motif, a [Cu-3(mu(3)-OH)(mu-Pyz)(3)] unit. The appearance of the SBU in five MOFs confirms the robustness and reproducibility of the motif with some interesting structures of various dimensionality ranging from 1D helical and 2D herringbone grid to a complex 3D framework. The deployment of bent acids brings chirality via helicity in the system, as further confirmed by solid-state CD spectra. A detailed investigation of the porous MOFs reveals their importance as zeolite analogues for environment remediation. MOF-1-MOF-5 show some interesting photodegradation of harmful organic dyes. MOF-4 and MOF-5 show impressive selective CO2 gas sorption properties. Furthermore, magnetic properties associated with the trinuclear and hexanuclear SBUs of MOF-1 and MOF-3-MOF-5 have also been investigated.